(3GdRghQ GdeTQbI hGdfaMGJ GdYHbIs - (3jhSa Hf CMeO Hf eMeO Hf YKeGfs
(3ChdgG (B:s
(3jHOC HcJGH GdTaYI Hbhdg (B: (3dgG eYfjGf dZI hEUWdGMkG , CeG ai GddZI agi s
(3BNQgG (B:s
(3bhdg ai GdSGHYI dG Gfg jLYd ESdGe GdeYJb TQWkG hEfeG EJaGb GdedI TQW ddejQGK , hUdi Gddg Ydi eMeO hBdg s
(3GdLRA GdKGdK ef fSNI CNQis
(3cJHJ GdYfGhjjf HGdMeQIs
(3Ydi MhGTjgG JYdjbGJs
(3GdfSNI HgG MhGT s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
Keywords: (3Gdabg GdESdGejs